2007
DOI: 10.1523/jneurosci.0775-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuits Mediate Electrosensory Behavior inCaenorhabditis elegans

Abstract: The nematode Caenorhabditis elegans deliberately crawls toward the negative pole in an electric field. By quantifying the movements of individual worms navigating electric fields, we show that C. elegans prefers to crawl at specific angles to the direction of the electric field in persistent periods of forward movement and that the preferred angle is proportional to field strength. C. elegans reorients itself in response to time-varying electric fields by using sudden turns and reversals, standard reorientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(160 citation statements)
references
References 50 publications
(56 reference statements)
11
148
0
1
Order By: Relevance
“…Femtosecond laser ablation was used to clarify precisely which neurons are involved in electrotaxis, from sensing electric fields to making reorientation decisions and to executing them [130]. The response of mock and post-surgery swimming worms to temporal variations of odor in their environment is consistent with aggregation phenotypes obtained in previous crawling assays [131].…”
Section: Eleganssupporting
confidence: 54%
“…Femtosecond laser ablation was used to clarify precisely which neurons are involved in electrotaxis, from sensing electric fields to making reorientation decisions and to executing them [130]. The response of mock and post-surgery swimming worms to temporal variations of odor in their environment is consistent with aggregation phenotypes obtained in previous crawling assays [131].…”
Section: Eleganssupporting
confidence: 54%
“…We found that in the presence of a velocity gradient next to stationary surface, most undulatory swimmers align themselves against the direction of the flow (positive rheotaxis) with their heads facing upstream. In contrast to other tactic behaviors, such as chemotaxis (26), thermotaxis (27), and electrotaxis (28), which require active involvement of the nervous system, rheotaxis results from purely mechanical interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the parasitic nematodes' ability to sense EF can be attributed to identification and interaction with host, it seems irrelevant for C. elegans to display galvanotaxis behavior as soil dueling organism. However, it can be explained that electrotactic response in C. elegans may be evolutionary conserved [27]. In spite of lacking understanding of basic mechanism of electrosensation by sensory neurons in C. elegans, as described above, our current understanding of the behavioral pattern of a simple model organism like C. elegans has resulted in application of this phenomenon to analyze various basic mechanisms of neuromuscular activities and related genes, to analysis the effect of toxic chemical and therapeutic compounds, to understand the benefit of exercise and to sort worm of particular population for research purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether suggesting a possible involvement of genetic basis as stark relation to electro-sensation behavior ( [26], through personal communication). Gabel et al (2007) attempted to understand more about the specific genetic and neuronal basis of C. elegans galvanotaxis as well as mapped the neuronal circuits involved in this behavior. They also found that the electrotaxis is a robust event, after the worms were subjected to EF and the worm moves at an angle toward the cathode.…”
Section: Elegans Electrotaxis Behaviormentioning
confidence: 99%
See 1 more Smart Citation